Thermoeconomic modeling of organic manure fertilizers in LATAM for sustainable and circular agriculture - Gomez Montoya, Juan Pablo; ORTIZ DONGO, Luis Felipe; SOLÓRZANO, Richard; ARRIETA GONZALES, CARLOS; LUNA DELRISCO, Mario; COAQUIRA TORRES, Edgar; ROJAS RIMBALDI, Jhuliana M. (LACCEI, 2025)
This document presents a thermoeconomic mathematical model to quantify the potential of bioenergy generation in Latin America (LATAM) under the circular economy approach. The study focuses on valorizing livestock manure, an abundant resource in the region, to produce biofertilizers and biogas, contributing to agricultural and energy sustainability. A calculation model estimates the number of biodigesters needed based on partial manure collection, considering each country's resource availability and energy needs. The model quantifies biogas production, a renewable energy source, and biofertilizers, which enhance soil fertility and reduce reliance on chemical fertilizers. Three types of biodigesters, adapted to different contexts and scales, were developed and field-tested, with results validated by Peru's Ministry of Agriculture, ensuring their real-world applicability. The biofertilizers produced meet agronomic standards, promoting organic agriculture. A thermoeconomic analysis assesses required investments and return on investment (ROI) rates, showing the technology's economic viability and profitability in the medium to long term, alongside environmental and social benefits. The research supports climate change mitigation by reducing methane emissions through biogas production and promoting sustainable agricultural practices with biofertilizers. It also enhances food security by boosting agricultural productivity and reducing dependency on external inputs. In conclusion, this work provides a robust tool for decision-making in LATAM's agricultural and energy sectors, promoting a transition to a circular economy and sustainable agriculture, aligned with the UN's Sustainable Development Goals (SDGs). Implementing these technologies offers opportunities for rural development, poverty reduction, and a more sustainable future for the region.